Gene mutations of platelet glycoproteins and response to tirofiban in acute coronary syndrome - Mansur, Antonio de Padua (2016)
CONTEXT AND OBJECTIVES: Glycoprotein inhibitors (abciximab, eptifibatide and tirofiban) are used in patients with unstable angina and non-ST-segment elevation myocardial infarction before percutaneous coronary intervention. Of these, tirofiban is the least effective. We hypothesized that the response to tirofiban might be associated with glycoprotein gene mutations. DESIGN AND SETTING: Prospective study at Emergency Unit, Heart Institute (InCor), University of São Paulo. METHOD: Intrahospital evolution and platelet aggregation in response to tirofiban were analyzed in relation to four glycoprotein mutations in 50 patients indicated for percutaneous coronary intervention: 17 (34%) with unstable angina and 33 (66%) with non-ST-segment elevation myocardial infarction. Platelet aggregation was analyzed using the Born method. Blood samples were obtained before and one hour after tirofiban infusion. Glycoproteins Ia (807C/T), Ib (Thr/Met), IIb (Ile/Ser) and IIIa (PIA) were the mutations selected. RESULTS: Hypertension, dyslipidemia, diabetes, smoking, previous coronary artery disease and stroke were similar between the groups. Mutant glycoprotein IIIa genotypes had lower platelet aggregation before tirofiban administration than that of the wild genotype (41.0% ± 22.1% versus 55.9% ± 20.8%; P = 0.035). Mutant glycoprotein IIIa genotypes correlated moderately with lower platelet inhibition (r = -0.31; P = 0.030). After tirofiban administration, platelet glycoprotein Ia, Ib, IIb and IIIa mutations did not influence the degree of inhibition of platelet aggregation or intrahospital mortality. CONCLUSIONS: Mutations of glycoproteins Ia, Ib, IIb and IIIa did not influence platelet aggregation in response to tirofiban in patients with unstable angina and non-ST-segment elevation myocardial infarction.